Forms of Pride in Vaižgantas’s Pragiedruliai - Kazarinova , Ksenija (Colloquia, 2020)
The author of the article analyzes the expression of pride in Juozas Tumas-Vaižgantas’s novel Pragiedruliai [Flashes]. She argues that pride, in addition to being employed as a rhetorical and stylistic device, becomes an axiological tool used to highlight society’s flaws that need to be corrected and to encourage the reader to take a stand against political and cultural injustice. The author discusses three main forms of pride. The first form is used to present the fallacies of the nobility. The social behavior of its representatives is often perceived as false pride in the novel. The author exposes this feature in Sviestavičius’s figure and shows the way how to release oneself from the patemic cage. In order to illustrate the ingrained ‘noble’ vanity, the article briefly discusses Vaižgantas’s early work, a short story Tėvo palikimas [Father’s Legacy], in which Matjošauckienė, doctor’s wife, blinded by false pride, destroys social and family ties and loses touch with reality. The portraits of characters, who are constructed by giving them attributes associated with the patemic behavior and consciousness of vanity, provide another context for the pride in Pragiedruliai. A detailed description of a cunning pharmacist Viadorelli is a good example of the second form of pride. Alongside such spiritually crippled characters, the writer juxtaposes positive features of intellectuals and enlightened peasants working for the benefit of Lithuania. The third form of pride is related to the specifics of the act of communication. In order to intensify verbal discourse and to express their disapproval of the political system, the characters in the novel act out a patemic play—they repeat external actions related to false pride.